The Malayan tapir - Mohd. Momin Khan 1935- (Big 5 Malaysian animal series, 2014)
The story of the Tapir is fascinating, as it is a species that did not attract the interest of hunters. The species was indirectly protected because of this lack of interest and recent studies have revealed that it is thriving in Malaysia forest, especially in protected areas. The population estimate is approximately 1,500 Tapirs. It is a big animal with rather short legs. The front paws have four toes and the hind paws have three. The height is about 1-1.2m at the shoulder.